[OP.6C.03] DO PATIENTS ACTUALLY DO WHAT WE ASK? PATIENT PERFORMANCE AND PERSISTENCE IN THE TASMIN-SR BLOOD PRESSURE SELF-MANAGEMENT TRIAL. (September 2016) - Schwartz, C.; Seyed-Safi, A.; Sayeed Haque, M.; Bray, E.; Greenfield, S.; Hobbs, R.; Little, P.; Mant, J.; Williams, B.; McManus, R.
Abstract : Objective: This study assessed how accurately patients reported their blood pressure (BP) and titrated their antihypertensive medications according to the protocol set out by the TASMIN-SR trial. Design and method: The TASMIN-SR self-management intervention involved patients with above target clinic BP and stroke, diabetes, CHD or CKD, self-monitoring their BP for the first week of every month followed by implementation of an individualised self-titration schedule. 276 patients were randomised to the intervention and 226 (80%) successfully completed 2 or 3 training sessions. Patients were followed up for 12 months and during this time submitted written records of home BP readings, and details of any medication changes made, on a monthly basis. BP readings were downloaded from each patient's monitor at 6 and 12 month follow-up clinics and these were compared to those submitted along with an assessment of protocol fidelity. Results: Of 226 patients who were successfully trained, 174 (77%) completed self-management. 10, 038/11, 684 (85.9% (95% CI, 85.3 – 86.5) of all readings submitted were reported accurately, when compared to the readings downloaded from the monitor, and 164 patients (95%) reported their readings with at least 80% accuracy. There was an average error rate of 6.7% per patient and the only characteristic affecting this was age, under 65 years compared to those above (4.5%, (95% CI 3.2 – 5.6) vs 7.7%, (95% CI 6.4 – 9.0), p < 0.005). In terms of protocol fidelity, 1811 (98%) of submitted records were sufficient to make a decision on whether a medication change was necessary according to the algorithm. Patients made 58.6% (370/631) of suggested medication changes, equating to 2.1/3.6 changes per patient. Baseline mean systolic BP for patients who completed the training was 143.1 mmHg. Mean 12 month systolic BP was 120.9 mmHg for patients who made all recommended changes, and 131.2 mmHg for patients who did not make any of the recommended changes, resulting in an overall mean SBP of 126.1 mmHg. Conclusions: In conclusion the majority of higher risk patients with hypertension successfully monitored and reported their home BP readings and persisted with the protocol over the study resulting in significantly lower BP.